The Moderating Role of Personal Trust on the Relationship between Nurses’ Social Skills and Need for Achievement in Arjomand and Razieh-Firoz Hospitals in 2014 - Beheshtifar, Malikeh; Moghadam, Mahmood Nekoei (Asian Journal of Social Sciences and Management Studies, 2016)
Employees who are motivated by success, enjoy challenging objectives, have good practice and perseverance and competitive spirit is evident in their business activities. Social skills needed to achieve success factor that can increase trust in people, can exacerbate this relation. Hence, the aim of this study was to investigate the relationship between nurses social skills and need for achievement, according to a moderating role of personal trust in Arjomand and Razieh-Firoz hospitals in 2014. In this study, correlational and cross-sectional method was used. The population of this study, consisted of nurses in Arjomand and Razieh-Firoz hospitals that the total number is 142 people. To determine the sample size of 100 people were chosen based on Morgan table. The study used three questionnaires: social skills questionnaire validity 0.98 and reliability 0.95 questionnaire need for achievement with validity 0.98 and reliability 0.93 and the questionnaire individual trust with reliability 0.96 and validity of 0.95. For data analysis, the approach of partial least squares (PLS) with software Smart PLS 2. used. The results showed that there is no relationship between the nurses social skills and need for achievement (and all its components) in Arjomand and Razieh-Firoz hospitals. Also, comparative ability component predict negative negligence. Also, there is no relationship between the nurses social and need for achievement (accountability component), due to the moderating role of individual trust in Arjomand and Razieh-Firoz hospitals, but there is relationship between nurses social skills and competitiveness, hard work and purpose oriented due to the mediating role of individual trust in Arjomand and Razieh-Firoz hospitals. Social skills are the ability to create constructive interactions among nurses that makes their relationship work better under its control and therefore committed to the progress and success, and confidence in the relationship can sometimes moderated. Therefore, the promotion of social skills and trust in the workplace considered.